Analysis of the lawn bowl trajectory as a teaching tool for sports engineering: Development of a graphical user-interface - Medwell, P. R.; Brooks, L. A.; Medwell, B. S. (Procedia Engineering, 2011)
Sports engineering graduates require a range of competencies. The ability to interactively process and analyse data is a useful skill that may not be fully covered in more traditional engineering subjects. One particular focus within this area that many graduates will find invaluable is the ability to write computer programmes incorporating a graphical user-interface (GUI). This paper outlines the development of a GUI in MATLAB® to interactively present the trajectory of a lawn bowl. Through the developed MATLAB® GUI, numerous parameters can be varied and the influence on the trajectory of a lawn bowl can be shown graphically. This practical example also provides an excellent opportunity to teach many other relevant aspects of MATLAB®. The skills that are introduced in this paper may readily be applied to a range of other sports engineering applications.